﻿A generic classification of Xenidae (Strepsiptera) based on the morphology of the female cephalothorax and male cephalotheca with a preliminary checklist of species - Benda, Daniel; Pohl, Hans; Nakase, Yuta; Beutel, Rolf; Straka, Jakub (ZooKeys, 2022)
The generic taxonomy and host specialization of Xenidae have been understood differently by previous authors. Although the recent generic classification has implied a specialization on the level of host families or subfamilies, the hypothesis that each xenid genus is specialized to a single host genus was also previously postulated. A critical evaluation of the classification of the genera of Xenidae is provided here based on morphology in accordance with results of recent molecular phylogenetic studies. External features of the female cephalothoraces and male cephalothecae were documented in detail with different techniques. Diagnoses and descriptions are presented for all 13 delimited genera. The earliest diverging genera are usually well characterized by unique features, whereas deeply nested genera are usually characterized by combinations of characters. Three new genera are described: Sphecixenos gen. nov., Tuberoxenos gen. nov., and Deltoxenos gen. nov. Five previously described genera are removed from synonymy: Tachytixenos Pierce, 1911, stat. res.; Brasixenos Kogan & Oliveira, 1966, stat. res.; Leionotoxenos Pierce, 1909, stat. res.; Eupathocera Pierce, 1908, stat. res.; and Macroxenos Schultze, 1925, stat. res. One former subgenus is elevated to generic rank: Nipponoxenos Kifune & Maeta, 1975, stat. res. Monobiaphila Pierce, 1909, syn. nov. and Montezumiaphila Brèthes, 1923, syn. nov. are recognized as junior synonyms of Leionotoxenos Pierce, 1909, stat. res. Ophthalmochlus Pierce, 1908, syn. nov., Homilops Pierce, 1908, syn. nov., Sceliphronechthrus Pierce, 1909, syn. nov., and Ophthalmochlus (Isodontiphila) Pierce, 1919, syn. nov. are recognized as junior synonyms of Eupathocera Pierce, 1908, stat. res. A preliminary checklist of 119 described species of Xenidae with information on their hosts and distribution is provided. The following 14 species are recognized as valid and restituted from synonymy: Tachytixenosindicus Pierce, 1911, stat. res.; Brasixenosacinctus Kogan & Oliveira, 1966, stat. res.; Brasixenosaraujoi (Oliveira & Kogan, 1962), stat. res.; Brasixenosbahiensis Kogan & Oliveira, 1966, stat. res.; Brasixenosbrasiliensis Kogan & Oliveira, 1966, stat. res.; Brasixenosfluminensis Kogan & Oliveria, 1966, stat. res.; Brasixenosmyrapetrus Trois, 1988, stat. res.; Brasixenoszikani Kogan & Oliveira, 1966, stat. res.; Leionotoxenoshookeri Pierce, 1909, stat. res.; Leionotoxenosjonesi Pierce, 1909, stat. res.; Leionotoxenoslouisianae Pierce, 1909, stat. res.; Eupathoceraluctuosae Pierce, 1911, stat. res.; Eupathoceralugubris Pierce, 1909, stat. res.; Macroxenospiercei Schultze, 1925, stat. res. New generic combinations are proposed for 51 species: Leionotoxenosarvensidis (Pierce, 1911), comb. nov.; Leionotoxenosbishoppi (Pierce, 1909), comb. nov.; Leionotoxenosforaminati (Pierce, 1911), comb. nov.; Leionotoxenosfundati (Pierce, 1911), comb. nov.; Leionotoxenoshuastecae (Székessy, 1965), comb. nov.; Leionotoxenositatiaiae (Trois, 1984), comb. nov.; Leionotoxenosneomexicanus (Pierce, 1919), comb. nov.; Leionotoxenosprolificum (Teson & Remes Lenicov, 1979), comb. nov.; Leionotoxenosrobertsoni (Pierce, 1911), comb. nov.; Leionotoxenostigridis (Pierce, 1911), comb. nov.; Leionotoxenosvigili (Brèthes, 1923), comb. nov.; Eupathoceraargentina (Brèthes, 1923), comb. nov.; Eupathoceraauripedis (Pierce, 1911), comb. nov.; Eupathocerabucki (Trois, 1984), comb. nov.; Eupathoceraduryi (Pierce, 1909), comb. nov.; Eupathoceraerynnidis (Pierce, 1911), comb. nov.; Eupathocerafasciati (Pierce, 1909), comb. nov.; Eupathocerafuliginosi (Brèthes, 1923), comb. nov.; Eupathocerainclusa (Oliveira & Kogan, 1963), comb. nov.; Eupathocerainsularis (Kifune, 1983), comb. nov.; Eupathoceramendozae (Brèthes, 1923), comb. nov.; Eupathocerapiercei (Brèthes, 1923), comb. nov.; Eupathocerastriati (Brèthes, 1923), comb. nov.; Eupathocerataschenbergi (Brèthes, 1923), comb. nov.; Eupathocerawestwoodii (Templeton, 1841), comb. nov.; Macroxenospapuanus (Székessy, 1956), comb. nov.; Sphecixenosabbotti (Pierce, 1909), comb. nov.; Sphecixenosastrolabensis (Székessy, 1956), comb. nov.; Sphecixenosdorae (Luna de Carvalho, 1956), comb. nov.; Sphecixenoserimae (Székessy, 1956), comb. nov.; Sphecixenosesakii (Hirashima & Kifune, 1962), comb. nov.; Sphecixenosgigas (Pasteels, 1950), comb. nov.; Sphecixenoskurosawai (Kifune, 1984), comb. nov.; Sphecixenoslaetum (Ogloblin, 1926), comb. nov.; Sphecixenosorientalis (Kifune, 1985), comb. nov.; Sphecixenosreticulatus (Luna de Carvalho, 1972), comb. nov.; Sphecixenossimplex (Székessy, 1956), comb. nov.; Sphecixenosvanderiisti (Pasteels, 1952), comb. nov.; Tuberoxenosaltozambeziensis (Luna de Carvalho, 1959), comb. nov.; Tuberoxenossinuatus (Pasteels, 1956), comb. nov.; Tuberoxenossphecidarum (Siebold, 1839), comb. nov.; Tuberoxenosteres (Pasteels, 1950), comb. nov.; Tuberoxenostibetanus (Yang, 1981), comb. nov.; Deltoxenosbequaerti (Luna de Carvalho, 1956), comb. nov.; Deltoxenosbidentatus (Pasteels, 1950), comb. nov.; Deltoxenoshirokoae (Kifune & Yamane, 1992), comb. nov.; Deltoxenosiwatai (Esaki, 1931), comb. nov.; Deltoxenoslusitanicus (Luna de Carvalho, 1960), comb. nov.; Deltoxenosminor (Kifune & Maeta, 1978), comb. nov.; Deltoxenosrueppelli (Kinzelbach, 1971a), comb. nov.; Xenosropalidiae (Kinzelbach, 1975), comb. nov. Xenosminor Kinzelbach, 1971a, syn. nov. is recognized as a junior synonym of X.vesparum Rossi, 1793. Ophthalmochlusduryi Pierce, 1908, nomen nudum and Eupathoceralugubris Pierce, 1908, nomen nudum are recognized as nomina nuda and therefore unavailable in zoological nomenclature. The species diversity of Xenidae probably remains poorly known: the expected number of species is at least twice as high as the number presently described.
Keywords: generic revision; wasp parasite; Xenidae; cephalothorax; wasps; taxonomy; Cephalotheca; morphology; Strepsiptera